A Field-Wide Metasynthesis of Pedagogical Research in Technical and Professional Communication. (January 2020) - Melonçon, Lisa; Rosselot-Merritt, Jeremy; St.Amant, Kirk
Pedagogical and programmatic research remains important in technical and professional communication. For such approaches to be effective, meaningful, and successful, they must represent effective scholarship that can be used within and address the needs of the greater field. The authors performed a metasynthesis of pedagogical and programmatic scholarship published in five central technical and professional communication journals between 2011 and 2015 ( n  = 82). The authors report the results of this research and what it means for the field to approach pedagogical and programmatic scholarship in the future.